Ethical Oversight of Research on Patient Care - Solomon, Mildred Z.; Bonham, Ann C. (The Hastings Center report, 2013)
The Institute of Medicine has called on health care leaders to transform their health systems into “learning health care systems,” capable of studying and continuously improving their practices. Learning health care systems commit to carrying out numerous kinds of investigations, ranging from clinical effectiveness studies to quality improvement research and implementation science. There has been progress in realizing the IOM's vision, but also many challenges. One of these challenges has been lingering uncertainty about whether the data collection and monitoring central to learning health care systems is actually research and if so, what kind of ethical oversight it should have. This is not a new question. Yet so far, there has been no foundational analysis of the fit between the existing human subjects protection framework in use in the United States and the new kinds of data collection activities that are being, and increasingly will be, undertaken by learning health care systems. Two companion feature articles in this volume, by a team at Johns Hopkins, fill this void.